2018
DOI: 10.1590/s0102-865020180040000007
|View full text |Cite
|
Sign up to set email alerts
|

Demineralized bone matrix and calcium-phosphate cement in bone regeneration in rats

Abstract: Purpose: To compare bone regeneration in critical-sized defects in rat calvarium using demineralized bone matrix and calcium phosphate cement. Methods: Thirty Wistar rats were divided into 3 groups of 10 animals each. Two defects of 5-mm were made in the parietal bones of each animal. Group I had calcium phosphate cement placed in the experimental defect, Group II had filled with demineralized bone matrix and Group III had with the combination of the matrix and cement in equal parts. All animals had one defect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
2
4
0
Order By: Relevance
“…Our results are similar to those in other studies in which DBM was implanted together with calcium phosphate cement, where the calcium phosphate cement acted by inhibiting osteogenesis when associated with a DBM [ 11 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results are similar to those in other studies in which DBM was implanted together with calcium phosphate cement, where the calcium phosphate cement acted by inhibiting osteogenesis when associated with a DBM [ 11 ].…”
Section: Discussionsupporting
confidence: 91%
“…DBM products are available in several commercial presentations, such as morselized material, powder, putty pastes, chips, porous foams, gel, etc. [ 10 , 11 , 12 ]. Nevertheless, a high osteogenic capacity rate of bone is lost while it is processed [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we compared osteogenic effects of TBC and DBM on femoral condyle and radial defects. The results indicated that the repair with xenograft bone scaffolds of 8 weeks were needed and the repair results were better than those of 4 weeks whatever the type of defects, which was in line with previous studies [ 19 , 34 ].…”
Section: Discussionsupporting
confidence: 91%
“…Cyanoacrylate has yet to be tested on bone repair outside of maxillofacial surgeries [7]. Demineralized bone matrix has shown promise in filling in defects in bone [8]. There has yet to be an effective glue combination with demineralized bone matrix without severely compromising the strength of the bonding adhesive [8].…”
Section: Discussionmentioning
confidence: 99%
“…Demineralized bone matrix has shown promise in filling in defects in bone [8]. There has yet to be an effective glue combination with demineralized bone matrix without severely compromising the strength of the bonding adhesive [8]. This combination of cyanoacrylate glue and demineralized bone matrix could provide the quick and simple repair needed for comminuted fractures.…”
Section: Discussionmentioning
confidence: 99%